ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA KARYAWAN PT. WIJAYA KARYA BETON, TBK SUMATERA UTARA - Dwi Enrica Sukatno; Eka Daryanto; Achmad Rifai (FKM Universitas Halu Oleo, 2021)
Personal protective equipment (PPE) is a tool that must be used when working according to work hazards and risks to maintain the safety of the workers themselves and those around them. PPE plays an important role in occupational safety and health. The purpose of this study was to determine the relationship between knowledge, attitudes, availability, regulations, and worker’s supervision of the compliance with the use of PPE on workers at PT.Wijaya Karya Beton. The design of this study used an analytic survey with a cross sectional approach. The sample in this study were 100 employees of PT Wijaya Karya Beton. The statistical test used was the chi square test and logistic regression. The results shows that of the total respondents, 51.0% were aged 23-38 years, 32.0% had high school education, 76.0% had worked for 11-30 years. The results of bivariate analysis using chi-square showed that knowledge (p = .000), attitude (p = .000), availability of PPE (p = .000), regulation (p = .000) and supervision (p = .000). From the multivariate analysis, the most influential factor in this study is the availability of PPE with an OR value of 47,300, which means that respondents whose availability of PPE is less likely to cause 47 times the non-compliance of respondents in using PPE. From the results of this study, it is hoped that the management of PT.Wijaya Karya, Tbk of North Sumatra will be able to better maintain their promotional efforts towards the use of personal protective equipment so that it can influence the knowledge and attitudes of workers to wear complete personal protective equipment and keep the condition of personal protective equipment in good condition before the replacement period is by adding a demonstration method for the use and care of personal protective equipment during the safety talk